Fertility drugs and the risk of breast cancer - Zreik, Tony (2010)
The risk of breast cancer has been associated with reproductive history. The purpose of this study was to determine the relationship between fertility drugs used in assisted reproductive procedures and the risk of breast cancer. We performed a literature search using the MEDLINE, the COCHRANE Library, and Scopus to identify studies linking breast cancer to fertility drugs. We excluded case series, case reports, and review articles from our analysis. The study populations included women who were treated for infertility with clomiphene, gonadotropins, gonadotropin-releasing hormones, or other unspecified fertility agents. We extracted information on study design, sample size, type of fertility drugs and number of treatment cycles, breast cancer incidence, and follow-up time from these studies. Eight case–control studies and fifteen cohort studies were included in the quantitative analyses. The Newcastle–Ottawa Quality Assessment Scales were used. Two investigators independently extracted study methods, sources of bias, and outcomes. We found that the risk of breast cancer was not significantly associated with fertility drug treatment. The follow-up periods were short in some of the studies analyzed in our study; however, we proceeded to test the trend in risk estimates across different durations of follow-up and found a trend for association using the nonparametric test; this was interpreted with caution in view of the lack of adjustment with other confounding factors. The current published data do not suggest higher risk of breast cancer in women who receive fertility treatment, but the lack of long-term follow up and the inherent weaknesses in some of the published studies have to be cautiously taken into account.